2006
DOI: 10.1243/09576509jpe172
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of Pongamia pinnata L. oil as a diesel substitute

Abstract: Present work deals with testing a performance of a compression ignition (CI) engine with different blends of non-edible oil as well as their methylesters with petrodiesel. Various blends of a non-edible vegetable oil, commonly known as honge (Pongamia pinnata L.) in India, were prepared and tested over a wide range of engine load. Results obtained from the study showed that 15 -20 per cent pongamia methylester-diesel blend (B15 and B20) could be a better fuel in terms of fuel efficiency and power developed. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 10 publications
2
33
0
Order By: Relevance
“…The literature showed that only few studies are available on effects of biodiesel in the LHR engine, an experimental study is needed with various biodiesel to identify best fuel for LHR engine. In this study, an experiment was carried out to characterize the performance, combustion and emission of pongamia methyl ester blends with diesel [18][19][20][21][22] and comparison was made with Al 2 O 3-coated and uncoated engines.…”
Section: Introductionmentioning
confidence: 99%
“…The literature showed that only few studies are available on effects of biodiesel in the LHR engine, an experimental study is needed with various biodiesel to identify best fuel for LHR engine. In this study, an experiment was carried out to characterize the performance, combustion and emission of pongamia methyl ester blends with diesel [18][19][20][21][22] and comparison was made with Al 2 O 3-coated and uncoated engines.…”
Section: Introductionmentioning
confidence: 99%
“…cetane number) of the fuel. Compression ratio, engine speed, cylinder gas pressure, temperature of the air intake and quality of fuel spray affect the ignition delay period [39]. In the case of DSPO-BD blends the start of combustion was delayed compared to FD at most load conditions.…”
Section: Combustion Characteristicsmentioning
confidence: 99%
“…Suryawanshi et al [18] experimented using blends of Pongamia methyl ester with diesel fuel and found a reduction in HC and CO (Carbon Monoxide) emissions at part loads as well as full load compared to diesel fuel. Grimaldi et al [19] concluded that BTE was found higher in blends of biodiesel compared to diesel fuel at high loads in a diesel engine.…”
Section: Tilak S R K Chandrashekara H Yogish and A M Maheshamentioning
confidence: 99%